IMF Staff Papers : Volume 10, No. 3. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1963)
This paper explains the features of the Communaute Financiere Africaine (CFA) Franc system. All CFA countries belong to one of three monetary systems. Although their statutes and functions differ somewhat, the three central banks have various common features. All three central banks are authorized to extend short-term and medium-term credit to the private sector. Many the commercial banks operating in the CFA countries are French banks with head offices in Paris. The credit operations of the commercial banks in the CFA countries are largely dependent upon the rediscount facilities offered by the central banks. The Bank is the sole authority for issuing CFA currency in the countries of French Equatorial Africa and in Cameroon. The exchange regulations applied in the CFA countries are patterned on those of France, with adaptations decided upon by local authorities according to local conditions and requirements. While exchange transactions with the other franc area countries generally are free, those with the non-franc area are subject to licensing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet